Global Political Demography The Politics of Population Change - Goerres, Achim; Vanhuysse, Pieter (Springer Nature, 2021)
This open access book draws the big picture of how population change interplays with politics across the world from 1990 to 2040. Leading social scientists from a wide range of disciplines discuss, for the first time, all major political and policy aspects of population change as they play out differently in each major world region: North and South America; Sub-Saharan Africa and the MENA region; Western and East Central Europe; Russia, Belarus and Ukraine; East Asia; Southeast Asia; subcontinental India, Pakistan and Bangladesh; Australia and New Zealand. These macro-regional analyses are completed by cross-cutting global analyses of migration, religion and poverty, and age profiles and intra-state conflicts. From all angles, this book shows how strongly contextualized the political management and the political consequences of population change are. While long-term population ageing and short-term migration fluctuations present structural conditions, political actors play a key role in (mis-)managing, manipulating, and (under-)planning population change, which in turn determines how citizens in different groups react.